The aerobic biological purification of the wastewaters from the organic contaminants (OC) in the aerotanks with the suspended and the fixed biocenosis - Oleynik, Aleksandr; Airapetian, Tamara (Lira-K, 2016)
The mathematical model and calculation methods of biological purification of the waste waters from organic contaminants (OC) in the aerotanks with the suspended (free flowing) biocenosis in the form of the flukes of the active sludge and with fixed biocenosis in the form of the biofilm generated on the surface of the additional loading are presented. The characteristic properties of the modeling and calculation of the purification in the aeration tank mixers and in the aeration tank with plug flow are considered.
Keywords: biological purification; organic contaminants; model; aerotank; biofilm; 628.356.3